A comparison of equivolume, equiosmolar solutions of hypertonic saline and mannitol for brain relaxation in patients undergoing elective intracranial tumor surgery: a randomized clinical trial - Dostal, Pavel; Dostalova, Vlasta; Schreiberova, Jitka; Tyll, Tomas; Habalova, Jirina; Cerny, Vladimir; Rehak, Svatopluk; Cesak, Tomas (Journal of neurosurgical anesthesiology, 2015)
BACKGROUND: Hyperosmolar solutions have been used in neurosurgery to modify brain bulk and prevent neurological deterioration. The purpose of the study was to compare the effects of equivolume, equiosmolar solutions of mannitol and hypertonic saline (HTS) on brain relaxation and postoperative complications in patients undergoing elective intracranial tumor surgery. METHODS: In this prospective, randomized study, patients with American Society of Anesthesiologists physical status I to III scheduled to undergo a craniotomy for intracranial tumors were enrolled. Patients received a 3.75 mL/kg intravenous infusion of either 3.2% HTS (group HTS, n=36) or 20% mannitol (group M, n=38). The surgeon assessed the condition of the brain using a 4-point scale after opening the dura. Recorded measures included duration of surgery, blood loss, urine output, volume and type of infused fluids, hemodynamic variables, electrolytes, glucose, creatinine, predefined postoperative complications, and length of intensive care unit and hospital stays. RESULTS: Brain relaxation conditions in group HTS (score 1/2/3/4, n=10/17/2/7) were better than those in group M (score 1/2/3/4, n=3/18/3/14, P=0.0281). Patients in group M had higher urine output, received more crystalloids during surgery, and displayed lower central venous pressure and lower natremia at the end of surgery than did patients in group HTS. No significant differences in postoperative complications or lengths of intensive care unit and hospital stays were observed between the groups. CONCLUSIONS: Our results suggest that HTS provides better brain relaxation than mannitol during elective intracranial tumor surgery.
Keywords: senioři; Brain Neoplasms; Blood Loss, Surgical; Length of Stay; mladiství; délka pobytu; Middle Aged; urodynamika; mužské pohlaví; Infusions, Intravenous; Blood Volume; mozek; intravenózní infuze; péče o pacienty v kritickém stavu; mladý dospělý; Adult; Critical Care; neurochirurgické výkony; Mannitol; Postoperative Complications; Prospective Studies; Craniotomy; Saline Solution, Hypertonic; krvácení při operaci; Brain; Young Adult; ženské pohlaví; kraniotomie; Humans; prospektivní studie; krevní objem; mannitol; lidé středního věku; nádory mozku; hypertonický solný roztok; Urodynamics; dospělí; Neurosurgical Procedures; Female; Aged; Preoperative Care; Adolescent; předoperační péče; pooperační komplikace; lidé; Male